Enhancing Driver Safety: A Smart and Secure Alert System for Road Hazards using Raspberry Pi Controller (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
This project presents a vehicle safety system implemented as a robotic car using Raspberry Pi and Arduino. The system incorporates various modules and sensors to address different aspects of road safety, including fog removal using Open CV and a camera, pothole detection and alert using Open CV camera, rain detection for automatic windshield wipers using a servo motor, identification of road special zones such as school zones and U-turn zones using RFID, displaying notifications on an LCD, and obstacle detection using an ultrasonic sensor to alert the driver. These integrated features work together to enhance safety and provide a comprehensive approach to road safety in diverse driving conditions. The fog removal module utilizes Open CV and a camera connected to the Raspberry Pi to capture images of the road. By applying image processing algorithms, the system can effectively remove fog or haze from the captured images, improving visibility for the driver and reducing the risk of accidents caused by reduced visibility in foggy conditions. By leveraging the capabilities of a Raspberry Pi controller and intelligent algorithms, it offers a valuable solution to mitigate potential risks and promote safer driving experiences. The system utilizes a Raspberry Pi controller as its central component. By integrating various sensors and employing intelligent algorithms, the system aims to enhance driver safety and provide real-time alerts to mitigate potential risks.